Value premium as a predictor of stock returns in China. - Wong, Nelson. (2011)
In this report, we investigate whether value premium exists and its predictive power of stock returns in the Chinese stock markets. Using data from the China Stock Market & Accounting Research Database (CSMAR), we examined three proxies to identify value stocks : book-to- market (B/M), price-earnings (P/E) and dividend yield (D/Y) ratios, and found that D/Y and B/M ratio do not predict stock returns in cross-sectional regressions. After removing D/Y from the portfolio formation, we found that value premium does exist in China stock markets and the magnitude of value premium increases with both portfolio holding periods and firm size. Notably, the value-premium effect is also more pronounced when we employ either the P/E or both the P/E and B/M ratio concurrently in the strategies instead of using only the B/M ratio.